'Delusional' consent in somatic treatment: the emblematic case of electroconvulsive therapy. Issue 6 (13th February 2020) - Bersani, Giuseppe; Pacitti, Francesca; Iannitelli, Angela
Abstract : Even more than for other treatments, great importance must be given to informed consent in the case of electroconvulsive therapy (ECT). In a percentage of cases, the symbolic connotation of the treatment, even if mostly and intrinsically negative, may actually be a determining factor in the patient's motives for giving consent. On an ethical and medicolegal level, the most critical point is that concerning consent to the treatment by a psychotic subject with a severely compromised ability to comprehend the nature and objective of the proposed therapy, but who nonetheless expresses his consent, for reasons derived from delusional thoughts. In fact, this situation necessarily brings to light the contradiction between an explicit expression of consent, a necessary formality for the commencement of therapy, and the validity of this consent, which may be severely compromised due to the patient's inability to comprehend reality and therefore to accept the proposal of treatment, which is intrinsic to this reality. With the use of an electric current, the symbolic experience associated with anaesthesia, and the connection to convulsions, ECT enters the collective consciousness. In relation to this, ECT is symbolic of these three factors and hooks on to the thoughts, fears, feelings and expectations of delusional patients. These are often exemplified in the violent intervention of the persecutor in the patient with schizophrenia, the expected punishment for the 'error' committed for which the depressed patient blames himself and the social repression of the maniacal patient's affirmation of his inflated self-esteem.